Model‐Based Comparison of Dose‐Response Profiles of Tofacitinib in Japanese Versus Western Rheumatoid Arthritis Patients - Suzuki, Misaki (J Clin Pharmacol, 2019)
Tofacitinib is an oral Janus kinase inhibitor for the treatment of rheumatoid arthritis (RA). The aim of this analysis was to characterize the relationship between tofacitinib dose and efficacy, as measured by American College of Rheumatology (ACR) response rates, and to compare this between Japanese and Western patients with RA. Efficacy data were pooled from 2 double‐blind, dose‐ranging phase 2 studies of tofacitinib monotherapy 1‐15 mg twice daily in patients with RA with an inadequate response to disease‐modifying antirheumatic drugs (DMARDs). NCT00550446 was carried out in mostly Western patients and NCT00687193 in Japanese patients. ACR20, ACR50, and ACR70 response rates in week 12 were analyzed using maximum drug effect (E(max)) models on the logit domain. Both studies showed a dose‐response for each end point, supporting the efficacy of tofacitinib in patients with inadequate response to DMARDs. Study‐specific differences in E(max) were noted, whereas potency (dose providing half the maximum effect [ED(50)]) was similar across studies. After adjustment for study differences in E(max) by calculating the fractions of the maximum placebo‐adjusted proportion of ACR responses, the estimated locations for the 5‐ and 10‐mg twice‐daily doses on the dose‐response curves were similar for the 2 patient populations: ACR20, ACR50, andACR70 mean fractional responses for 5 and 10 mg twice daily were 0.78, 0.43, 0.32 and 0.90, 0.69, and 0.56, respectively, for the Japanese study and 0.54, 0.41, and 0.22 and 0.73, 0.61, and 0.40, respectively, for the Western study. This analysis therefore supports the rationale for the same dosing regimen in Japanese patients as in Western patients from an efficacy perspective.